PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI, TERHADAP PERTUMBUHAN EKONOMI DAERAH PROVINSI DI KAWASAN TIMUR INDONESIA - Asrudi rudy; samel w ririhena (Musamus Journal of Economics Development, 2019)
As a developing country, economic growth is an output formed by various economic sectors so that it can describle the development or the decline of economic sector in certain time period. Thes study aims to describe the direct an indirect effect government expenditure and investment on the economic growth through regional competitivnes in all provinces in eastern Indonesia. The research used government expenditure, domestic investment (PMDN), regional competitiveness, and economic growth as the date. The were used to describe the influence of dependent variabel (government expenditure, and investment) on the independent variabel (economic growth) and intervening variable (regional competitiveness). The results show that there is a positive and significant direct influence of government expenditure (x1) on economic growth (y2), and there is a positive and significant direct influence of investment (x2) on economic growth (y2). However in terms of the indirect influence of government expenditure and investment on economic growth through regional competitiveness, there is no significant effect. It can be concluded that government expenditure and investment can directly influence economic growth positively and significantly. However, there is no significant indirect impact of government expenditure and investment on economic growth through regional competitiveness. Keywords: government expenditure, investment, economic growth, regional competitivness